An Environmental History of Southern Malawi - Morris, Brian. author. aut Link
XXI, 343 p. 10 illus.
Keywords: This book is a pioneering and comprehensive study of the environmental history of Southern Malawi. With over fifty years of experience, anthropologist and social ecologist Brian Morris draws on a wide range of data – literary, ethnographic and archival – in this interdisciplinary volume. Specifically focussing on the complex and dialectical relationship between the people of Southern Malawi, both Africans and Europeans, and the Shire Highlands landscape, this study spans the nineteenth century until the end of the colonial period. It includes detailed accounts of the early history of the peoples of Northern Zambezia; the development of the plantation economy and history of the tea estates in the Thyolo and Mulanje districts; the Chilembwe rebellion of 1915; and the complex tensions between colonial interests in conserving natural resources and the concerns of the Africans of the Shire Highlands in maintaining their livelihoods. A landmark work, Morris’s study constitutes a major contribution to the environmental history of Southern Africa. It will appeal not only to scholars, but to students in anthropology, economics, history and the environmental sciences, as well as to anyone interested in learning more about the history of Malawi, and ecological issues relating to southern Africa.